2016
DOI: 10.1002/jor.23461
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dysplasia of the hip: A computational biomechanical model of the path of least energy for closed reduction

Abstract: This study utilized a computational biomechanical model and applied the least energy path principle to investigate two pathways for closed reduction of high grade infantile hip dislocation. The principle of least energy when applied to moving the femoral head from an initial to a final position considers all possible paths that connect them and identifies the path of least resistance. Clinical reports of severe hip dysplasia have concluded that reduction of the femoral head into the acetabulum may occur by a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These muscles are relaxed and may not prevent reduction when the dislocated hip is flexed with the hip abducted in the Pavlik harness. A previous study analyzed the contributions of these muscles and confirmed negligible effects relative to the muscles included in the model (Ardila et al, 2013;Zwawi et al, 2016). For this study, musculoskeletal tissue was modeled using a straight-line muscle path representation since lines of action do not intersect in the range of motion of interest and it allowed usage of classic methods of vector analysis (Dostal and Andrews, 1981).…”
Section: Three-dimensional Lower Extremity Model Of Ten-week Old Female Infantmentioning
confidence: 66%
See 3 more Smart Citations
“…These muscles are relaxed and may not prevent reduction when the dislocated hip is flexed with the hip abducted in the Pavlik harness. A previous study analyzed the contributions of these muscles and confirmed negligible effects relative to the muscles included in the model (Ardila et al, 2013;Zwawi et al, 2016). For this study, musculoskeletal tissue was modeled using a straight-line muscle path representation since lines of action do not intersect in the range of motion of interest and it allowed usage of classic methods of vector analysis (Dostal and Andrews, 1981).…”
Section: Three-dimensional Lower Extremity Model Of Ten-week Old Female Infantmentioning
confidence: 66%
“…A patient-derived Rigid Body Dynamics computational model of the lower extremity of a ten-week old female infant previously developed Zwawi et al, 2016) was modified to include a range of FA angles. The infant age was selected because it represents an age where the lower limb is sensitive to deformation due to a severe dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…And limit the displacement of the distal femur in three dimensions. To avoid the effect of asymmetric bones on the results, we did not model muscles and ligaments, Considering that we are simulating the conditions of static standing, a previous study analyzed the contributions of these muscles and con rmed negligible effects relative to the muscles included in the model (Ardila et al 2013;Zwawi et al 2017). The rest of the model C and D are obtained by similar methods.…”
Section: Loading and Sensitivity Studiesmentioning
confidence: 99%